Application of The Rotary Dryer Machine in The Semi Modern Herbal Herbs Business Group in Nguter District, Sukoharjo Regency - Sartono Putro (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The purpose of this community service program is to apply the rotary dryer unit to the production of herbal herbs that do not require solar heat. Target on the management aspect, partners are able to manage business with standard business management. Partners have an entrepreneurial spirit and have a strong spirit. Activities are carried out with coordination and discussion with partners. A meeting to determine the capacity of the rotary dryer unit and the needs of electrical energy and heat sources. Whereas for the herbal medicine business entrepreneur group, coordination was carried out to determine the material and motivation management training to foster an entrepreneurial spirit. The rotary dryer unit consists of two main parts, namely: air heater and rotary dryer cylinder. Air heater is made from a range of 3/4 inch diameter mild steel pipes, while the shell wall is made of mild steel plates with 1.2 mm thickness. For air plants centrifugal blowers are used with a 2 inch pipe diameter. A heat source is used by a single burner with LPG fuel. The rotary dryer cylinder, is a concentric tube, from a perforated stainless steel plate used as a place for dried simplicia. While the outer tube is made of mild steel plates. The tube is rotated using a 200 Watt one pasha electric motor. Improved business management with standard management to improve marketing efficiency and development.